Wireless Wearable Photoplethysmography Sensors for ContinuousBlood Pressure Monitoring - Zhang,Y; Berthelot,M; Lo,BPL (IEEE, 2016)
Blood Pressure (BP) is a crucial vital sign takeninto consideration for the general assessment of patient’s condition:patients with hypertension or hypotension are advisedto record their BP routinely. Particularly, hypertension isemphasized by stress, diabetic neuropathy and coronary heartdiseases and could lead to stroke. Therefore, routine andlong-term monitoring can enable early detection of symptomsand prevent life-threatening events. The gold standard methodfor measuring BP is the use of a stethoscope and sphygmomanometerto detect systolic and diastolic pressures. However,only discrete measurements are taken. To enable pervasiveand continuous monitoring of BP, recent methods have beenproposed: pulse arrival time (PAT) or PAT difference (PATD)between different body parts are based on the combinationof electrocardiogram (ECG) and photoplethysmography (PPG)sensors. Nevertheless, this technique could be quite obtrusiveas in addition to at least two contacts/electrodes to measurethe differential voltage across the left arm/leg/chest and theright arm/leg/chest, ECG measurements are easily corruptedby motion artefacts. Although such devices are small, wearableand relatively convenient to use, most devices are not designedfor continuous BP measurements. This paper introduces anovel PPG-based pervasive sensing platform for continuousmeasurements of BP. Based on the principle of using PAT toestimate BP, two PPG sensors are used to measure the PATDbetween the earlobe and the wrist to measure BP. The device iscompared with a gold standard PPG sensor and validation ofthe concept is conducted with a preliminary study involving 9healthy subjects. Results show that the mean BP and PATD arecorrelated with a 0.3 factor. This preliminary study shows thefeasibility of continuous monitoring of BP using a pair of PPGplaced on the ear lobe and wrist with PATD measurements ispossible.